Characterization of Extracellular Vesicles Isolated From Human Milk Using a Precipitation-Based Method - Bickmore, Diana C.; Miklavcic, John J. (Frontiers in Nutrition, 2020)
Extracellular vesicles (EV) in human milk may confer immunologic benefits to infants. Methods of EV isolation such as ultracentrifugation (UC) may not be feasible for the study of EVs in human milk due to the difficulty of acquiring large sample volumes. A technique to isolate EVs from a small volume of human milk using a commercial precipitation kit is described herein. Electron microscopy, nanoparticle tracking analysis, and semi-quantitative antibody array were used to confirm isolation of human milk EVs. Size, protein content, and fatty acid quantification of EVs were also determined. This isolation technique yielded 8.9 x 10^9 EV particles/mL of human milk. The present method meets the Minimal Information for Studies of Extracellular Vesicles (MISEV) guidelines. An established EV isolation method suitable for a low volume of human milk will facilitate further research in this growing area.